Literary Analysis of Figurative Symbolism in Tembang Oghem Macapat as Social Forecast Manner used by Madura Societies - Rohaniyah, Jaftiyatur (International Journal of English Education and Linguistics (IJoEEL), 2020)
Macapat is one of the ancient old culture existed in Madura especially in some villages in Pamekasan. This was became uninterested culture among society nowdays, exactly for millennial generation. In spite of this, this culture is still sustained by Madura society. Macapat has a beautiful song or tembang in every steps of meaning. The manuscript contain the legend of Prophet Muhammad and his Sohabah. The manuscript of Macapat is usually used as a forecast manner in making prediction of problem solving by Madurese people in Larangan Luar Village. This is showed ‘Oghem’ as a part of Macapat. The song of macapat generally use figurative language and symbolism to show the hidden meaning in the manuscript. Then, it is analyzed as literary analysis in socio-cultural approach. This research use qualitative method in deep observasion approach. There are two focus of research: the way of societies in doing forecast and the literary analysis of symbolism in the Song of Oghem Macapat. This research purposed to have deep understanding of Literature in Social aspect of culture. The result of the research was clearly explained and found that society belief about oghem as a way to give real contribution for their social life. While the symbolism of macapat was found as figurative symbol of situation which was implied in the song.